Catalytic activity vs. size correlation in platinum catalysts of PEM fuel cells prepared on carbon black by different methods - Nores Pondal, Federico Jose (2009)
In this work nanoparticulated platinum catalysts have been prepared on carbon Vulcan XC-72 using three methods starting with chloroplatinic acid as a precursor: (i) formic acid as a reductor agent; (ii) impregnation method followed by reduction in hydrogen atmosphere at moderated temperature; and (iii) microwave-assisted reduction in ethylene glycol. The catalytic and size studies were also performed on a commercial Pt catalyst (E-Tek, De Nora). The characterization of the particle size and distribution was performed by means of transmission electron microscopy (TEM) and X-ray diffraction (XRD). The characterizations of the catalytic and electrocatalytic properties of the catalysts were determined by studying the cyclohexane dehydrogenation reaction (CHD) and the behavior under cyclic voltammetry (CV) in sulfuric acid solutions. The measured electrochemical activity, along with the hydrogen chemisorption of the catalysts allows the estimation of effective particle sizes, which are much larger than those measured by TEM and XRD. The catalysts prepared by reduction with formic acid and ethylene glycol (microwave-assisted) show electrochemical activities very close to those of the commercial catalyst, and are almost insensitive to the Pt dispersion or Pt particle size. The chemical activity in CHD correlates well with the metallic dispersion determined by hydrogen chemisorption, indicating similar accesibility of H2 and cyclohexane to the catalyst surface.